Low circulatory Fe and Se levels with a higher IL-6/IL-10 ratio provide nutritional immunity in tuberculosis - Kaushik, Sandeep R.; Sahu, Sukanya; Guha, Hritusree; Saha, Sourav; Das, Ranjit; Kupa, Rukuwe-u; Kapfo, Wetetsho; Deka, Trinayan; Basumatary, Rumi; Thong, Asunu; Dasgupta, Arunabha; Goswami, Bidhan; et al. (Frontiers in Immunology, 2023)
Tuberculosis (TB) patients show dysregulated immunity, iron metabolism, and anaemia of inflammation. In this study, circulatory cytokines, trace metals, and iron-related proteins (hepcidin, ferroportin, transferrin, DMT1, Nramp1, ferritin, ceruloplasmin, hemojuvelin, aconitase, transferrin receptor) were monitored in case (active tuberculosis patients: ATB) and control (non-tuberculosis: NTB and healthy) study populations (n=72, male: 100%, 42.94 years mean age (17-83)). Using serum elemental and cytokine levels, a partial least square discriminate analysis model (PLS-DA) was built and variables with a VIP score of >0.6 were selected as important markers. A biosignature of IL-13, IL-12(p70), IFN-, IL-10, IL-5, IL-18, IL-4, Selenium, and Aluminium clustered ATB subjects away from controls. Interestingly, low iron and selenium levels, while high copper and aluminium levels were observed in ATB subjects. Low circulatory levels of transferrin, ferroportin, and hemojuvelin with higher ferritin and ceruloplasmin levels observed in ATB subjects demonstrate an altered iron metabolism in ATB patients which partially resolved upon 6 months of anti-TB therapy. The identified biosignature in TB patients demonstrated perturbed iron homeostasis with anemia of inflammation which could be useful targets for the development of host-directed adjunct therapeutics.